APPLICATION OF ULTRAVIOLET C IRRADIATION FOR THE INCREASED PRODUCTION OF SECONDARY METABOLITES IN PLANTS - Awdhesh K. Mishra; Seong-Jin Choi; Kwang-Hyun Baek (Journal of Animal and Plant Sciences, 2020)
Ultraviolet C (UV-C) irradiation is an excellent method for the induction of secondary metabolites in many plants. Thus far, various types of secondary metabolites have been induced by the application of different doses of UV-C irradiation either alone or in combination with other treatments. Especially, the treatment of a low dose of UV-C for up to 30 min allows the plants to partially recover to their normal physiological status and triggers the key enzymes of their metabolic pathway, ultimately leading to considerable increase in secondary metabolite. Increased levels of secondary metabolite vary from plant to plant. Apart from that, they also play crucial roles in UV protection. In this review, we will discuss various aspects of the accumulation of plant secondary metabolites by the irradiation of UV-C.
Keywords: Secondary metabolite; UV-C radiation; flavonoids; carotenoids